The analysis of modyficated mono equation - Švitra, Donatas; Retkutė, Renata (Lietuvos matematikos rinkinys, 1999)
The differential equation with dalay:Ń(t) = α (N(t - h))/(1 +(N(t-h)/K)n) - βN(t),  n > 1is proposed to model blood cells dynamics. The basic qualities of solutions of this equation are considered.